2017
DOI: 10.1002/2017rg000564
|View full text |Cite
|
Sign up to set email alerts
|

In‐flight dynamics of volcanic ballistic projectiles

Abstract: Centimeter to meter‐sized volcanic ballistic projectiles from explosive eruptions jeopardize people and properties kilometers from the volcano, but they also provide information about the past eruptions. Traditionally, projectile trajectory is modeled using simplified ballistic theory, accounting for gravity and drag forces only and assuming simply shaped projectiles free moving through air. Recently, collisions between projectiles and interactions with plumes are starting to be considered. Besides theory, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 142 publications
(351 reference statements)
0
45
0
1
Order By: Relevance
“…Comparing with other studies, metric-size ballistic projectiles are not typical of Strombolian and Sub-Plinian activity and are more common during Vulcanian explosions [Maeno et al 2013;Bombrun et al 2015;Taddeucci et al 2017]. Based on the size/velocity inverse relationship [Bombrun et al 2015], the maximum launching velocities observed for metric-size projectiles at Tungurahua are higher than those expected for Strombolian activity (<100 m s −1 for >0.6-m-diameter blocks) with velocities up to 117-135 m s −1 , 143-162 m s −1 and 144-153 m s −1 for January, May-June and November eruptions respectively.…”
Section: Eruptive Style and Hazard Assessmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Comparing with other studies, metric-size ballistic projectiles are not typical of Strombolian and Sub-Plinian activity and are more common during Vulcanian explosions [Maeno et al 2013;Bombrun et al 2015;Taddeucci et al 2017]. Based on the size/velocity inverse relationship [Bombrun et al 2015], the maximum launching velocities observed for metric-size projectiles at Tungurahua are higher than those expected for Strombolian activity (<100 m s −1 for >0.6-m-diameter blocks) with velocities up to 117-135 m s −1 , 143-162 m s −1 and 144-153 m s −1 for January, May-June and November eruptions respectively.…”
Section: Eruptive Style and Hazard Assessmentmentioning
confidence: 94%
“…In the distribution histogram, the outer values (<-30 m and >+40 m) represents only 11.5% of all trajectories and could be associated to trajectories modified by processes such as block fragmentation and collision processes during flight [Vanderkluysen et al 2012;Tsunematsu et al 2014;Taddeucci et al 2017]. This amount of abnormal trajectories is significantly higher than the value obtained by Dürig et al [2015] for the Eyjafjallajökull 2010 eruption (97 clast-clast collisions over thousands of ejecta) but it is consistent when taking into account the metric-size of the projectiles for Tungurahua's case.…”
Section: Hazard Assessment Of Volcanic Ballistic Projectilesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot estimate the drag coefficient from this process. Taddeucci et al (2017) estimated the drag coefficient value based on their observation using the high-speed camera. The maximum value of the drag coefficient, calculated using the averaged particle velocity and the flow velocity by Taddeucci et al (2017), was very large (e.g., C D > 3.0).…”
Section: Gas Flow and Drag Effectmentioning
confidence: 99%
“…In Strombolian eruptions, pyroclast ejection shows significant variability in observed velocities and dynamics, which are thought to be strongly influenced by initial conditions, such as depth of slug bursting (Dürig et al, 2015; Taddeucci et al, 2017), size and amount of particles (Bonadonna & Costa, 2013; Carcano et al, 2014), and conduit and vent geometry (Ogden, 2011; Wilson et al, 1980). Linking the conduit processes (e.g., acceleration and velocity of the particles and their coupling with the gas) to the associated source parameters is an important target, since they control eruptive dynamics, including, for example, particle velocity and ejection angle (Houghton et al, 2004; Kennedy et al, 2005; Pioli et al, 2009), and have strong implications for volcanic ballistic hazard assessment.…”
Section: Introductionmentioning
confidence: 99%